Plasmacytoid dendritic cells sense hepatitis C virus-infected cells, produce interferon, and inhibit infection - Takahashi, Ken; Asabe, Shinichi; Wieland, Stefan; Garaigorta, Urtzi; Gastaminza, Pablo; Isogawa, Masanori; Chisari, Francis V (Proceedings of the National Academy of Sciences - PNAS, 2010)
Hepatitis C virus (HCV), a member of the Flaviviridae family, is a single-stranded positive-sense RNA virus that infects >170 million people worldwide and causes acute and chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Despite its ability to block the innate host response in infected hepatocyte cell lines in vitro, HCV induces a strong type 1 interferon (IFN) response in the infected liver. The source of IFN in vivo and how it is induced are currently undefined. Here we report that HCV-infected cells trigger a robust IFN response in plasmacytoid dendritic cells (pDCs) by a mechanism that requires active viral replication, direct cell-cell contact, and Toll-like receptor 7 signaling, and we show that the activated pDC supernatant inhibits HCV infection in an IFN receptor-dependent manner. Importantly, the same events are triggered by HCV subgenomic replicon cells but not by free virus particles, suggesting the existence of a novel cell-cell RNA transfer process whereby HCV-infected cells can activate pDCs to produce IFN without infecting them. These results may explain how HCV induces IFN production in the liver, and they reveal a heretofore unsuspected aspect of the innate host response to viruses that can subvert the classical sensing machinery in the cells they infect, and do not infect or directly activate pDCs.